GENETIC VARIABILITY STUDIES IN POTATO (SOLANUM TUBEROSUM L.) - Basavaraj, N; Naik, N. R.; Naik, K. S.; Gayatri, G. N. (Potato Journal, 2013)
Potato (Solanum tuberosum L.) is one of the most important food crop after rice, wheat and maize. Information on nature and magnitude of variability in the existing plant material and the association among the various characters is pre-requisite for improvement in the yield. The bio-metrical approaches used in the present investigations for studying variability include phenotypic and genotypic variances, coefficient of variation, heritability (bs) and genetic advance. The experiment was laid out on a randomized complete block design with two replications, consisting of 100 accessions from CPRI, Shimla at the AICRP (potato) centre, Dharwad during kharif 2003 and 2004. Seed tubers of 100 accessions along with check varieties Kufri Chandramukhi, JH-222, Kufri Pukhraj were planted in the second fortnight of June, maintaining a spacing of 60 cm from row to row and 20 cm from plant to plant. Analysis of variance revealed significant mean sum of squares for the 6 characters studied indicating the presence of sufficient genetic variation among the genotypes. The phenotypic coefficient of variation ranged from 25.33 for plant height to as high as 77.09 for tuber yield/plant. Similarly the genotypic coefficient of variation ranged from 10.60 for number of stems per plant to 48.41 for tuber yield. The results of the present investigations revealed that plant height, number of tubers per plant, tuber weight per plant, tuber yield per plant exhibited moderate to higher phenotypic and genotypic coefficient of variation as well as moderate to higher heritability coupled with higher genetic advance as per cent of the mean. Finaly it could be concluded that there exists a lot of genetic variation among the entries and improvement could be brought through simple selection.